Effects of uninterrupted dabigatran on the intensity of anticoagulation during atrial fibrillation ablation. Issue 1 (19th November 2021) - Osawa, Takumi; Mori, Hitoshi; Kawai, Akane; Kawano, Daisuke; Tsutsui, Kenta; Ikeda, Yoshifumi; Yamaga, Mitsuki; Sato, Atsushi; Gatate, Youdou; Hamabe, Akira; Tabata, Hirotsugu; Kato, Ritsushi; et al.
Abstract: Background: Uninterrupted dabigatran during atrial fibrillation (AF) ablation is now established as the standard therapy. However, there are few reports on the effects of uninterrupted dabigatran on the intensity of anticoagulation during AF ablation. Methods: We retrospectively analyzed 247 consecutive patients who underwent AF ablation in our hospital from January 2017 to December 2018. Patients who took warfarin or uninterrupted direct oral anticoagulants (DOACs) except for dabigatran were excluded. 89 patients underwent ablation with uninterrupted dabigatran (uninterrupted group, male 71, mean age 59.6 ± 14.0) and 124 with interrupted DOACs (interrupted group, male 105, mean age 56.9 ± 12.9) during AF ablation. The initial ACT level, proportion of ACT levels of more than 300 s, and total amount of heparin were compared. Furthermore, the incidence of procedure complications was also evaluated. Results: The initial ACT levels were significantly higher in the uninterrupted group, and the total number of ACTs of more than 300 s was significantly higher in the uninterrupted group (uninterrupted vs. interrupted; initial ACT level, 315.6 ± 59.8 vs. 264.5 ± 48.6, p < .001; total number of ACTs ≧300, n [%], 304/ 484 [62.8 %] vs. 372/745 [49.9%], p < .001). The total amount of heparin during procedure was significantly lower in the uninterrupted group (uninterrupted group vs. interrupted group; 12966 ± 4773 vs. 16371 ± 5212, p < .001). There was no significant difference in the incidence of complications between the two groups. Conclusions: In the catheter ablation of AF, uninterrupted dabigatran would be useful to obtain a stable anticoagulation status during the entire procedure. Abstract : The ACT levels during the procedure were significantly higher in the uninterrupted group. The percentage of ACT levels of more than 300 during the procedure was significantly higher in the uninterrupted group.